Pengaruh penerapan buku ajar bermuatan kecerdasan komprehensif dan model problem based learning pada materi gerak parabola dan gerak melingkar di kelas X SMAN 8 Padang - Wahyumin Kurnia Illahi; ramli ramli (PILLAR OF PHYSICS EDUCATION, 2020)
Learning outcomes in students Physics subjects are not as expected, due to students' mastery of Physics material is still lacking. Besides that the learning model used is still not varied and teaching materials are not yet fully used. Therefore, researchers used a Problem Based Learning (PBL) learning model supported by a textbook. This study aims to determine the effect of the application of textbooks containing comprehensive intelligence Model Problem Based Learning on Parabolic and Circular Motion material in class X of SMAN 8 Padang.This type of research is a quasi-experimental research design with pre-expertal design. The study population was all students of class X MIPA SMAN 8 Padang who were registered in 2019/2020. The research sample was taken using purposive sampling technique. The sample in this study was class X MIPA 3 as an experimental class and class X MIPA 5 as a control class. Research data are only knowledge competencies. The research instrument was in the form of pre-test and post-test questions to measure knowledge competence. The data obtained were analyzed using the two average similarity test (t test), simple linear regression test, and correlation test at the 0.05 level for knowledge competence.From the analysis of the data it can be concluded that the use of textbooks with comprehensive intelligence gives a significant difference to the knowledge competence of students at the real level of 0.05.